Perancangan dan Implementasi Jaringan VPN Dengan Metode L2TP/IPSec pada Kantor Cabang dan Kantor Pusat - Bambang Febrianto (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
PT. BICOM MITRA SOLUSINDO is a business entity that was established in early 2008 which focuses on providing IT services to customers, one of the customers where to access data and applications branch office employees need to come to the location so it is very inefficient and takes a long time. Based on these problems, the researchers are interested in conducting a research entitled "DESIGN AND IMPLEMENTATION OF VPN NETWORKS WITH L2TP/IPSEC METHODS AT THE CAANG OFFICE AND THE HEAD OFFICE". This information system is made with the L2TP VPN method so that branch offices and head office are connected to each other so that the results of this study can assist the company in accessing data or accounting applications.